2001
DOI: 10.1177/002215540104900510
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Localization of Secretory Phospholipase A2-like Protein in the Pituitary Gland and Surrounding Tissue of the Bullfrog, Rana catesbeiana

Abstract: S U M M A R YPreviously, we obtained a protein that has considerable amino acid sequence homology with secretory phospholipase A 2 (PLA 2 ) from a bullfrog pituitary fraction obtained during the purification of thyrotropin (TSH). Subsequently, partial amino acid sequence (N-terminal 45 amino acid residues) analysis revealed this protein to be identical to the N-terminal amino acid sequence of otoconin-22, the major protein of aragonitic otoconia in the Xenopus saccule. In this study we developed an antibody ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…In stage 25 (early stage) embryos with a head length of 3 and 5 mm, the endolymphatic sac displayed follicular structures consisting of a single epithelium, which reacted strongly with the DIG-labeled cRNA probe and anti-otoconin-22 serum (Figures 2d and 2e). A positive reaction was observed in the apical cytoplasm of the epithelial cells, which is consistent with the results obtained in the adult (Yaoi et al 2001).…”
Section: Expression Of Otoconin-22 Mrna and Proteinsupporting
confidence: 91%
See 1 more Smart Citation
“…In stage 25 (early stage) embryos with a head length of 3 and 5 mm, the endolymphatic sac displayed follicular structures consisting of a single epithelium, which reacted strongly with the DIG-labeled cRNA probe and anti-otoconin-22 serum (Figures 2d and 2e). A positive reaction was observed in the apical cytoplasm of the epithelial cells, which is consistent with the results obtained in the adult (Yaoi et al 2001).…”
Section: Expression Of Otoconin-22 Mrna and Proteinsupporting
confidence: 91%
“…The lumen of these sacs contains many tiny crystals consisting of calcium carbonate, which are formed by otoconin-22 protein. In a previous study, we found that otoconin-22 protein is present in the endolymphatic sac surrounding the pituitary gland and the paravertebral lime sac in the bullfrog (Yaoi et al 2001). Later, we cloned and sequenced a cDNA encoding bullfrog otoconin-22 and found that calcitonin regulates the expression of otoconin-22 mRNA in the endolymphatic sac, thereby stimulating the formation of calcium crystals in the lumen of the endolymphatic sac (Yaoi et al 2003b).…”
mentioning
confidence: 99%
“…Antisera were raised in rabbits immunized with the ST-170 or ST-173 peptides coupled to keyhole limpet hemocyanin (KLH) with m-maleimidobenzoyl-N-hydroxysuccinimide ester (MBS; Pierce, Rockford, Ill.) as described previously (Tanaka and Kurosumi, 1992). The antibody against bullfrog otoconin-22 protein, prepared and characterized as described by Yaoi et al (2001), was a guinea pig antiserum against a synthetic peptide corresponding to N-terminal amino acids 1-13 (ST-135: TPAQFDEMIKVTT) of bullfrog otoconin-22.…”
Section: Antibodiesmentioning
confidence: 99%
“…The lumen of these sacs contains many tiny crystals composed of calcium carbonate. Yaoi et al (2001) determined that otoconin-22 protein is present in the ELS surrounding the pituitary gland and the PVLS in the bullfrog. Otoconin-22 is believed to be important in creating conditions that favor nucleation and, subsequently, in controlling the crystal growth of the calcium carbonate lattice in otoconia (mineral particles embedded in the otolithic membrane).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, mechanisms for localized concentrations of the reactants are required, a role generally played by acidic glycoproteins in other carbonate-based calcification systems. Each type of otoconia is characterized by a distinct set of proteins collectively named otoconins (2)(3)(4). Interestingly, the major proteins of otoconia are related to the secretory phospholipase A2 (2)(3)(4).…”
mentioning
confidence: 99%